EVcas Lamp, innovation by UMPSA researchers, transforms streetlight poles into electric vehicle chargers - Safriza, Baharuddin; Hardyana, Mohd.Saman (UMPSA, 2025)
PEKAN, 6 October 2025 – Two researchers from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Dr. Wan Muhammad Noor Sarbani Mat Daud from the Faculty of Mechanical and Automotive Engineering Technology (FTKMA), and Ts. Dr. Muhammad Ikram Rashid from the Faculty of Electrical and Electronic Engineering Technology (FTKEE) and Automotive Engineering Centre (AEC), successfully developed an innovation named EVcas Lamp, an electric vehicle (EV) charging system integrated directly into streetlight poles.